Price of Onions: the lighter side of everyday economics - Desai, Ashok V. (New Delhi, 2001)
In this book, the first of its kind, Krishna Kumar explains how the history texts of both countries selectively narrate incidents or refrain from doing so for various ideological and cultural reasons. In order to show how widely the two perceptions vary, the author compares the textbooks currently used in Indian and Pakistani schools. He examines the representation of major episodes - like the 1857 rebellion, Independence and Partition - and the portrayal of personalities like Gandhi and Jinnah. The last part of the book analyses essays written on Partition by Indian and Pakistani schoolchildren.
Keywords: Economic problems